PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU SMP NEGERI 4 SURAKARTA - Sunarso, Titik Nuroini Rahayuningsih, Amin Wahyudi & (Universitas Slamet Riyadi, 2016)
The result of this research showed (1) The culture organization influential not significant toward the performance of the teachers in SMP Negeri 4 Surakarta, (2) Work environment significant toward the performance of the teachers in SMP Negeri 4 Surakarta, (3) The commitment organization influential significant toward the performance of the teachers in SMP Negeri 4 Surakarta, (4) The most dominant variable influential on the performance of the teachers in SMP Negeri 4 Surakarta is work environment, (5) The result of the test (F test) is chorused known magnitude of the value of F = 30,381 significant 0,000 < 0,05, so it can be concluded in with the same variable of culture organization, work environment, and commitment organization influence the performance of the teachers in SMP Negeri 4 Surakarta, Keywords: culture organization, work environment, organization commitment, teachers performance.